ANALISIS KORELASI KUALITAS INSTITUSI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Hardianto, Florentinus Nugro (Universitas Lancang Kuning, 2024)
The relationship between institutional quality and economic growth still raises dilemma because there is no definitive conclusion about the relationship between the two. On the one hand, the quality of institutions has a positive influence on economic growth, but on the other hand, it explains the negative influence of institutional quality on economic growth. This article aims to analyze the correlation between institutional quality and economic growth in Indonesia. This study uses two main variables, namely institutional quality and economic growth. This study uses the Pearson correlation test as a tool for analyzing data for his research using secondary data in the period 2003-2022. This study concluded that the rule of law variable did not have a significant relationship with the economic growth variable, the regulatory quality variable did not have a significant relationship with the economic growth variable, and the government effectiveness variable had a significant relationship with the economic growth variable.